The microbiome and lung cancer - Maddi, Abhiram; Sabharwal, Amarpreet; Violante, Timothy; Manuballa, Sunita; Genco, Robert; Patnaik, Santosh; Yendamuri, Sai (Journal of Thoracic Disease, 2019)
It has become increasingly clear that we live in a symbiotic relationship with microbes within us. We are just beginning to unravel the nature and strength of this relationship and its impact on both physiology and by extension, pathology. While microorganisms have long been known to have carcinogenic potential, their role may have been underestimated. The knowledge of the role of the microbiome in carcinogenesis is rapidly evolving. This evolution has reached a tipping point with current omics technologies used for cataloguing the microbiome. The lung is an organ constantly exposed to the environment. It is now clear that the lung has a distinct microbiome and that this may influence the development of lung cancer. In addition, evidence suggests that this microbiome originates from the oral microbiome. This review summarizes current knowledge about the role of microbiome, especially the oral and lung microbiome in human lung cancer. The goal of the manuscript is to provide a summary of this rapidly evolving field while providing a context of the general role of the microbiome in carcinogenesis. In addition, a primer of the current technology used in evaluating the microbiome is provided to familiarize the practicing clinician with the experimental methods used to generate the information that will likely impact the field of lung cancer.